Utilization of the American Corner collection at the Andalas University Library - gema putra islami (Literatify: Trends in Library Developments, 2022)
Abstrak The purpose of this study was to determine the utilization of the American Corner collection in the Andalas University Library. This research is a type of qualitative research with descriptive method through documentation by conducting interviews and analyzing internal factors consisting of: needs, motives, and interests as well as external factors consisting of: collection skills, librarian skills, and information retrieval. The results of the study are as follows. First, American Corner is a special service that is integrated in the college library. American Corner is the best corner service among other corner services in Andalas University library. This is supported by the facilities provided by the American Corner, the Andalas University library is widely used by students to make assignments, a place to rest and as a place of entertainment. That's good, because the recreation function of the library is executed. Second, internal factors are the fact that many students read collections to practice their English knowledge and are more interested in magazine and novel collections. Most students choose the American Corner because of the facilities provided, but many of the collections at the American Corner are not according to the student's interests so that it has an impact with books that are never touched and read by students. External factors should be added to the collection from the American Corner, but according to the needs and interests of students and the location of the computer, the OPAC retrieval system from the American Corner should be in the American Corner room to make it easier for students to retrieve information.